Layered tellurides: stacking faults induce low thermal conductivity in the new In2Ge2Te6 and thermoelectric properties of related compounds. Issue 36 (6th September 2017) - Lefèvre, Robin; Berthebaud, David; Lebedev, Oleg; Pérez, Olivier; Castro, Célia; Gascoin, Stéphanie; Chateigner, Daniel; Gascoin, Franck
Abstract : A new ternary layered compound In2 Ge2 Te6, belonging to the hexatellurogermanate family has been synthesized from the reaction of appropriate amounts of the pure elements at high temperature in sealed silica tubes. Abstract : A new ternary layered compound In2 Ge2 Te6, belonging to the hexatellurogermanate family has been synthesized from the reaction of appropriate amounts of the pure elements at high temperature in sealed silica tubes. In2 Ge2 Te6 crystallizes in the rhombohedral space-group R 3̄:H with lattice parameters a = 7.0863(3) Å and c = 21.206(2) Å and its structure is resolved using single crystal X-ray diffraction. The transport properties (Seebeck coefficient, resistivity and thermal conductivity) of compounds belonging to the family AMTe3 (A = In and Cr; M = Ge and Si) are reported. All compounds are p-type semiconductors. InSiTe3 and Cr2 Si2 Te6 are too resistive to be good thermoelectric materials, with maximal power factors of 10 −6 and 10 −5 W m −2 K −2 at 473 K, while In2 Ge2 Te6 and Cr2 Ge2 Te6 exhibit maximal values of about 10 −4 and 10 −3 W m −2 K −2 at 673 K, respectively. All compounds exhibit thermal conductivity below 2 W m −1 K −1, with values dropping to 0.35 W m −1 K −1 at 673 K for In2 Ge2 Te6 . Transmission electron microscopy evidences stacking faults explaining such low thermal conductivities. The best ZT values are observed for Cr2 Ge2 Te6 with 0.45 at 773 K and In2 Ge2 Te6 with 0.18 at 673 K. Among these layered structures, a spark plasma sintered Cr2 Ge2 Te6 sample exhibits some thermal conductivity anisotropy but only weakly due to crystallite orientations.